ANALISIS EFISIENSI PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DI PROPINSI SUMATERA BARAT - Rizka Afiyah Trisyandi; Hasdi Aimon; Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
This study is to measure the level of efficiency of education spending at school age during 2013 and 2014 in West Sumatra. Determine the level of efficiency of education spending at school age and school operational assistance (BOS) during 2013 and 2014 in West Sumatra. Determine the level of efficiency of education spending at school age, school operational assistance, the ratio of teachers to students during 2013 and 2014 in West Sumatra.The type of this research is descriptive and quantitative.The method used in this research is data envelopment analysis (DEA). The research variable consists of input and output variables. The results of this research explains that the level of the high efficiency of government spending on the education sector in the West Sumatra, although there are some districts and cities that are not efficient. Keywords: Education spending at school age, BOS, ratio of teachers to students,  Efficiency and DEA